2022
DOI: 10.1002/smll.202204767
|View full text |Cite
|
Sign up to set email alerts
|

New Folding 2D‐Layered Nitro‐Oxygenated Carbon Containing Ultra High‐Loading Copper Single Atoms

Abstract: merits from both homogenous catalysts such as high atomic utilization efficiency and uniform active sites, and of heterogeneous catalysts, namely good stability, facile separation, and regeneration altogether. [1] Moreover, down-sizing metal particles to an atomically-dispersed form greatly increases the surface energy of the metals, resulting in pronounced catalytic reactivity. [2] Both theoretical and experimental investigations reveal the unusually high catalytic performance of SACs over conventional and na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Then, the mixture was placed in a quartz boat that was closed with a lid and pyrolyzed at 800 °C (ramp rate = 10 °C·min –1 ) in a tube furnace under an Ar atmosphere (flow rate = 200 sccm). Note that metal loading contents can be adjusted by tuning the ratios of M-Phc:Dicy:urea as described in detail in our previous report . Basically, urea tends to carry a higher metal loading than Dicy, as it is a smaller molecule with high N and O contents that are beneficial for anchoring isolated metal atoms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the mixture was placed in a quartz boat that was closed with a lid and pyrolyzed at 800 °C (ramp rate = 10 °C·min –1 ) in a tube furnace under an Ar atmosphere (flow rate = 200 sccm). Note that metal loading contents can be adjusted by tuning the ratios of M-Phc:Dicy:urea as described in detail in our previous report . Basically, urea tends to carry a higher metal loading than Dicy, as it is a smaller molecule with high N and O contents that are beneficial for anchoring isolated metal atoms.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the ratio between M-Phc:Dicy:urea should be optimized to achieve high metal loading and well-exfoliated 2D nanosheets. For example, 15.9 wt % Cu loading content with a suitably exfoliated 2D structure could be achieved when the weight ratio of M-Phc:Dicy:urea of 1:5:5 was used . Nevertheless, some metals are supposed to form clusters more easily than the others, depending on the nature of the metals.…”
Section: Methodsmentioning
confidence: 99%
“…[48] Copyright 2019, American Chemical Society; Reproduced with permission. [49] Copyright 2022, Wiley-VCH. pyrolysis method.…”
Section: High-temperature Pyrolysis Methodsmentioning
confidence: 99%
“…Cu-N/PC has excellent ORR catalytic activity with an E 1/2 of 0.91 V (vs RHE) in 0.1 m KOH solution (Figure 3d). Butburee et al [49] reported for the first time a new class of Cu-based SACs (F2DS-Cu) with a new 2D layered nanostructure. Cu-based SACs with high Cu loading (15.9 wt%) were obtained by one-step pyrolysis of a mixture of copper phthalocyanine (CuPc), urea, Reproduced with permission.…”
Section: High-temperature Pyrolysis Methodsmentioning
confidence: 99%
“…[253,254] The study of highloading single atoms is of great significance for improving the performance of ORR catalysts, understanding the catalytic mechanism, and promoting its application. [164,255,256] For example, Yamauchi developed a Fe-N 4 SACM with 8.36 wt.% metal loading using the molten salt exfoliation method to anchor Fe-N 4 on ultrathin 2D graphene with abundant defects. [257] Xu et al synthesized a SACM of 14.0 wt.% Co loading by a sacrificial template strategy with layered g-C 3 N 4 as a sacrificial template.…”
Section: High Load Engineeringmentioning
confidence: 99%